Is the Term Premium a Risk Premium? - Ederington, Louis H. (Institutional Knowledge at Singapore Management University, 1999)
This paper explores whether excess holding period returns on long vis-a-vis short-term securities behave in a manner that is consistent with (1) market efficiency, (2) the time-varying-term-premium variant of the expectations hypothesis, and (3) theories of the term premium that view it as a reward for risk bearing. Both traditional and modern theories of the term premium imply that it should evolve fairly slowly over time as attitudes toward risk and/or perceived covariances with wealth or consumption change. This implies that this period's term premium should have some predictive ability for next period's. However, we find that this quarter's ex-post term premium has zero predictive ability. For monthly rates and returns, the evidence is less clear cut, but again the implied term premia do not behave in a manner consistent with existing theories.